Prenatal maternal distress associates with a blunted cortisol response in rhinovirus-positive infants - Korhonen L.; Kortesluoma S.; Lukkarinen M.; Peltola V.; Pesonen H.; Pelto J.; Tuulari J.; Lukkarinen H.; Vuorinen T.; Karlsson H.; Karlsson L. (Elsevier Ltd, 2022)
Introduction: Prenatal exposure to maternal psychological distress (PD) may have programming effects on the fetus/infant hypothalamic-pituitary-adrenal (HPA) axis and subsequently on the development of the fetus’ immune function. Therefore, our aim was to study whether prenatal exposure to PD is related to early infant HPA axis reactivity in the context of a subclinical rhinovirus infection that challenges infants HPA axis postnatally.
Methods: This study included 336 10-week-old infants from the nested case control Focus Cohort of the FinnBrain Birth Cohort Study. The outcome was infant HPA axis reactivity in a stress test. The acute stressor comprised of pediatric examination with venipuncture and nasal swabs for virus assessment. Saliva cortisol samples were collected at 5 time points: baseline, 0, 15, 25 and 35 min after the stressor. HPA axis reactivity was defined by the cumulative post-stressor cortisol concentration.
Results: HPA axis reactivity was blunted in the PD/rhinovirus + group compared to the average of control/rhinovirus+, PD/rhinovirus-, and control/rhinovirus- groups (difference: 14.7 ln [nmol/L] × min, 95% confidence interval 3.8–25.6, p =  .008). HPA axis reactivity was significantly blunted only in boys with rhinovirus detected when separately tested for boys and girls (p =  .04).
Conclusion: Our finding of PD-exposed rhinovirus-positive infants having blunted cortisol secretion gives rise to a hypothesis that maternal PD during pregnancy influences infant HPA axis functioning and the functioning of the immune system. Future studies are needed to test whether this suppression of the HPA axis that co-occurs with rhinovirus infection associates with later disease development (e.g., asthma).